Assessment of Health-related Quality of Life in Cancer Patitients Receiving Chemotherapy in Specialist Hospital, Jalingo, North Eastern of Nigeria - Abdulganiyu Giwa; Carene Sabum; Halima Bukola Giwa; Muslim Olakunle Jamiu (Tehran University of Medical Sciences, 2021)
Background: This study aimed to assess Health-Related Quality of Life (HRQoL) in cancer patients receiving chemotherapy in Specialist Hospital, Jalingo, North-Eastern Nigeria, in 2015. Methods: A cross-sectional study was conducted on 218 cancer patients selected by systematic random sampling method. The study data were collected using a modified European Organization for Research and Treatment of Cancer QoL Questionnaire (EORTC QLQ-C30 v. 3). Results: Out of the 218 participants, 42(18.8%) had between 1 to 4 chemotherapy cycles, while 86(39.4%) had 5 to 8 cycles and the remaining 91(41.7%) had 9 to 12 chemotherapy cycles. There was a significant relationship between HRQoL and the number of chemotherapy cycles received. Conclusion: Encouraging cancer patients to complete a chemotherapy course plays an essential role in the treatment outcome and the HRQoL in cancer patients undergoing chemotherapy.